Flexible intrinsic heat-conducting polysiloxane composite material and preparation method thereof
By using boron nitride nanosheets of different particle sizes as fillers in polysiloxane composite materials, an efficient thermal conductivity path was constructed, which solved the problems of low thermal conductivity of polysiloxane and poor orientation effect of single particle size fillers, and achieved the efficient thermal conductivity and flexibility characteristics of the composite materials.
Patent Information
- Application Number
- CN202510070273.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
AI Technical Summary
The existing polysiloxanes have low thermal conductivity and poor orientation effect of single particle size fillers, making it difficult to meet the needs of efficient and rapid thermal conductivity.
Boron nitride nanosheets (BNNs) of different particle sizes are used as thermal fillers to build a more efficient thermal conductivity path through composites, and combined with the matrix of flexible intrinsic thermal conductivity polysiloxane composite materials to prepare composite materials with excellent thermal conductivity and flexibility characteristics.
It significantly improves the thermal conductivity of composite materials, imparts flexibility and low density, and at the same time improves volume resistivity to meet the needs of efficient thermal conductivity.
Smart Images

Figure CN119798673A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a flexible intrinsically thermally conductive polysiloxane composite material and a preparation method thereof. Background Art
[0002] The unique organic-inorganic hybrid molecular structure of polysiloxane gives it many properties superior to traditional rubber, such as high and low temperature resistance, low glass transition temperature, weather resistance, wear resistance, electrical insulation, flame retardancy, high chemical stability and physiological inertness. Since its commercialization in the 1940s, polysiloxane has been widely used in various industries such as aerospace, national defense, automobiles, construction, electronics, medical and food processing. For example, it is used as thermal interface materials for electronic devices, elastic bonding, positioning, heat dissipation, insulation and sealing in industries such as automobiles and instruments, and has attracted much attention in the field of thermal conductive materials.
[0003] The thermal conductivity (λ) of ordinary polysiloxane is around 0.2W / (m·K), which cannot meet the requirements of efficient and fast thermal conductivity. In previous research work, researchers have found that adding small molecule liquid crystal primitives during the cross-linking process of polysiloxane can effectively improve its thermal conductivity. This is because liquid crystal primitives can form local ordered domains in the cross-linked structure of polysiloxane, which improves the orderliness of the cross-linked structure and thus improves its thermal conductivity. However, the polysiloxane prepared by this method is mixed with some residual liquid crystal primitives due to incomplete reaction, and it is not easy for small liquid crystal molecules to achieve a good orientation effect, which limits the degree of improvement of λ in the prepared intrinsic thermal conductive polysiloxane.
[0004] Studies have shown that when the amount of thermal conductive filler is the same, the thermal conductivity of the composite material prepared by the high thermal conductive matrix is much higher than that of the composite material prepared by the low thermal conductive matrix. Boron nitride nanosheets (BNNs) are a 2D flaky thermal conductive material (λ>700W / (m·K)) with good insulation properties, excellent chemical stability and low cost. Yoshihara et al. used synthesized biphenyl liquid crystal polyester (LCPE) as the matrix and BNNs as the thermal conductive filler to prepare BNNs / LCPE thermal conductive composite materials by melt polycondensation-injection molding process. The results show that when the volume fraction of BNNs is 30vol%, the λ of the BNNs / LCPE thermal conductive composite material is ∥ and λ ⊥ The λ values of the thermal conductive composite materials are 11.5W / (m·K) and 2.5W / (m·K), which are much higher than that of the thermal conductive composite materials of BN / polybutylene terephthalate (PBT) at the same dosage. ∥ (5.0W / (m·K)) and λ ⊥(0.64W / (m·K)). However, a single filler often does not have a good thermal conductivity. By compounding BNNs of different particle sizes, a more efficient thermal conduction path can be constructed, effectively improving the efficiency of heat flow conduction, thereby improving the thermal conductivity of the composite material.
[0005] Therefore, it is urgent to study the effect of the composite of thermally conductive fillers with different particle sizes on the thermal conductivity of the flexible intrinsic thermally conductive polysiloxane composite matrix, so as to prepare an intrinsic thermally conductive polysiloxane composite with better λ. Summary of the invention
[0006] In order to overcome the technical problems of low intrinsic thermal conductivity of polysiloxane and poor orientation effect of single particle size filler in the prior art, the purpose of the present invention is to provide a flexible intrinsic thermal conductive polysiloxane composite material with BNNs of different particle sizes as thermal conductive fillers and a flexible intrinsic thermal conductive polysiloxane composite material as a matrix and a preparation method thereof. The composite material has excellent thermal conductivity, flexibility, low density and high volume resistivity.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present application provides a flexible intrinsically thermally conductive polysiloxane composite material, the structural formula of the flexible intrinsically thermally conductive polysiloxane composite material is as follows:
[0009]
[0010] Among them, the value range of n is 0 to 182, the value range of m is 0 to 182, and the value range of p is 23 to 45.
[0011] In combination with the first aspect, preferably, the number average molecular weight of the flexible intrinsically thermally conductive polysiloxane composite material is 50,000-100,000.
[0012] In combination with the first aspect, preferably, the relationship between n and m is n+m=182.
[0013] A second aspect of the present application provides a flexible intrinsically thermally conductive polysiloxane composite material, comprising the following steps:
[0014] Dissolving 4,4-dihydroxybiphenyl, 6-bromo-1-hexene and a basic catalyst in a first organic solvent, and performing a dehydrobromination reaction to obtain a first compound;
[0015] Boron nitride nanosheets BNNs with different particle sizes, a first compound, vinyl-terminated polydimethylsiloxane, a hydrosilylation catalyst and dimethyl methyl hydrogen are subjected to a siloxane addition reaction to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0016] In combination with the second aspect, preferably, the molar ratio of the 4,4-dihydroxybiphenyl to the 6-bromo-1-hexene is 10:20-23;
[0017] The molar ratio of the 4,4-dihydroxybiphenyl to the alkaline catalyst is 10:20-23.
[0018] In combination with the second aspect, preferably, the alkaline catalyst is one or more of potassium carbonate and potassium iodide;
[0019] The first organic solvent is acetone;
[0020] The hydrosilylation catalyst is one or more of chloroplatinic acid, Karstedt's catalyst and chloroplatinic acid complex.
[0021] In combination with the second aspect, preferably, the molar ratio of the first compound to the vinyl-terminated polydimethylsiloxane is 1:0.5;
[0022] The molar ratio of the sum of the molar amounts of the first compound and the vinyl-terminated polydimethylsiloxane to the dimethyl methyl hydrogen (siloxane to polysiloxane) is 1.4 to 1.6:1;
[0023] The molar ratio of the first compound to the hydrosilylation catalyst is 9.5-10.5:0.1;
[0024] The ratio of the weight of the boron nitride nanosheets to the total weight of the vinyl-terminated polydimethylsiloxane, dimethylmethyl hydrogen (siloxane and polysiloxane) and the first compound is 10-30:90-70.
[0025] In combination with the second aspect, preferably, the temperature for the dehydrobromination reaction is 60° C., and the reaction time is 12-24 hours;
[0026] The temperature for the silicon-oxygen addition reaction is 110-120° C., and the reaction time is 6-12 hours.
[0027] The preparation method of the flexible intrinsically thermally conductive polysiloxane composite material comprises adding BNNs of different particle sizes into the intrinsically thermally conductive polysiloxane twice, which are the first batch and the second batch respectively; the weight ratio of the first batch and the second batch under the dosage ratio of BNNs of different particle sizes is 1:9, 3:7, 5:5, 7:3 and 9:1.
[0028] The particle size of the boron nitride nanosheets with different particle sizes is 1 μm to 15 μm.
[0029] Furthermore, the particle sizes of different boron nitride nanosheets BNNs are 1 μm and 10 μm, which are abbreviated as nBNNs and mBNNs, respectively.
[0030] The third aspect of the present invention provides a thermally conductive composite material, comprising the flexible intrinsic thermally conductive polysiloxane composite material described in the first aspect or the flexible intrinsic thermally conductive polysiloxane composite material prepared by the method described in the second aspect.
[0031] Compared with the prior art, the beneficial effects of the present invention include at least:
[0032] The flexible intrinsically thermally conductive polysiloxane composite material provided by the present invention contains a benzene ring, a biphenyl group (rigid mesogen) and a silicon-oxygen-silicon chain (flexible chain) in its structural unit, and the molecular chain is locally ordered. The flexible polysiloxane main chain has a large free volume and molecular weight; the stacking of the rigid biphenyl group side chains and the π-π stacking structure between molecules inhibit the random orientation of the molecular chain and promote the formation of ordered domains of the layered structure. By compounding BNNs of different particle sizes, a more efficient heat conduction path can be constructed to improve the efficiency of heat flow conduction. The present invention uses BNNs of different particle sizes as fillers and a flexible intrinsically thermally conductive polysiloxane composite material as a matrix to prepare a flexible intrinsically thermally conductive polysiloxane composite material, giving the composite material excellent thermal conductivity and flexibility; at the same time, the composite material of the present invention has low density and high volume resistivity.
[0033] The preparation method of the flexible intrinsic thermal conductive polysiloxane composite material provided by the present invention first uses 4,4-dihydroxybiphenyl, 6-bromo-1-hexene and an alkaline catalyst as main raw materials, and synthesizes a small molecule liquid crystal monomer through a dehydrobromination reaction; the dehydrobromination reaction product is subjected to a hydrosilylation reaction with a vinyl-terminated polydimethylsiloxane, a hydrosilylation catalyst and dimethylmethyl hydrogen (siloxane and polysiloxane) to prepare an intrinsic high thermal conductive polysiloxane, and a flexible intrinsic thermal conductive polysiloxane composite material is prepared by compounding with BNNs of different particle sizes as fillers. On the one hand, the stacking of the rigid biphenyl group side chains and the π-π stacking structure between molecules inhibit the random orientation of the molecular chain, thereby promoting the formation of ordered domains of the layered structure. On the other hand, the compounding of BNNs of different particle sizes can construct a more efficient thermal conductive path, improve the thermal conductivity of the composite material, and give it low density and high volume resistivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A hydrogen nuclear magnetic resonance spectrum of the first compound provided in an embodiment of the present invention;
[0035] Figure 2 Polarized light microscope photographs of the flexible intrinsically thermally conductive polysiloxane composite material prepared in Example 1, wherein (a) is at room temperature, (b) is at the crystal melting temperature, and (c) is above the crystal melting temperature.
[0036] Figure 3These are SEM photos of the flexible intrinsically thermally conductive polysiloxane composite materials prepared in Examples 1-5, wherein (a)-(e) correspond to nBNNs:mBNNs=1:9, 3:7, 5:5, 7:3 and 9:1, respectively, and the mass fraction of nBNNs / mBNNs (i.e., the percentage of the thermally conductive filler in the total mass of vinyl-terminated polydimethylsiloxane, dimethyl methyl hydrogen (siloxane and polysiloxane) and the first compound) is 30wt%.
[0037] Figure 4 The volume resistivity of the flexible intrinsically thermally conductive polysiloxane composite material prepared in Examples 1-5. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings. The described embodiments should not be regarded as limiting the present invention. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0039] In the following description, reference is made to "some embodiments", which describe a subset of all possible embodiments, but it is understood that "some embodiments" may be the same subset or different subsets of all possible embodiments, and may be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present invention have the same meaning as those commonly understood by those skilled in the art to which the embodiments of the present invention pertain. The terms used in the embodiments of the present invention are only for the purpose of describing the embodiments of the present invention and are not intended to limit the present invention.
[0040] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0041] It should be noted that all raw materials / reagents in the embodiments of the present invention can be purchased on the market or prepared according to conventional methods well known to those skilled in the art; the term "and / or" in the embodiments of the present invention is only used to describe the association relationship between associated objects, indicating that three relationships may exist, for example, A and / or B means the existence of A alone, B alone, and A and B at the same time, wherein A and B can be singular or plural, and the character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0042] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0043] Those skilled in the art should understand that in the following description of the embodiments of the present invention, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0044] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "an" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0045] It will be appreciated by those skilled in the art that the numerical ranges in the embodiments of the present invention are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the range. Each smaller range between the intermediate values in any stated value and stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.
[0046] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the embodiments or test cases of the present invention. All documents mentioned in this specification are generally incorporated by reference to disclose and describe methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of the present invention shall prevail.
[0047] It should be noted that all raw materials and / or reagents in the examples of the present invention are purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0048] In a first aspect, the structural formula of the flexible intrinsically thermally conductive polysiloxane composite material provided by the embodiment of the present invention is as follows:
[0049]
[0050] In a specific embodiment, the number average molecular weight of the flexible intrinsically thermally conductive polysiloxane composite material in the embodiment of the present invention is preferably 50,000-100,000, more preferably 75,000-100,000, and further preferably 90,000-100,000.
[0051] The flexible intrinsically thermally conductive polysiloxane composite material provided by the present invention contains a benzene ring, a biphenyl group (rigid mesogen) and a silicon-oxygen-silicon chain (flexible chain) in its structural unit, and the molecular chain is locally ordered. The flexible polysiloxane main chain has a large free volume and molecular weight; the stacking of the rigid biphenyl group side chains and the π-π stacking structure between molecules inhibit the random orientation of the molecular chain and promote the formation of ordered domains of the layered structure. By compounding BNNs of different particle sizes, a more efficient heat conduction path can be constructed to improve the efficiency of heat flow conduction. The present invention uses BNNs of different particle sizes as fillers and a flexible intrinsically thermally conductive polysiloxane composite material as a matrix to prepare a flexible intrinsically thermally conductive polysiloxane composite material, giving the composite material excellent thermal conductivity and flexibility; at the same time, the composite material of the present invention has low density and high volume resistivity.
[0052] In a second aspect, an embodiment of the present invention provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material using BNNs of different particle sizes as thermally conductive fillers and a flexible intrinsically thermally conductive polysiloxane composite material as a matrix, the preparation method comprising the following steps S10 to S20:
[0053] S10: dissolving 4,4-dihydroxybiphenyl, 6-bromo-1-hexene and a basic catalyst in a first organic solvent, and performing a dehydrobromination reaction to obtain a first compound;
[0054] S20: BNNs of different particle sizes, the first compound and vinyl-terminated polydimethylsiloxane are uniformly mixed, dimethyl methyl hydrogen (siloxane and polysiloxane) and a hydrosilylation catalyst are added to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0055] It should be noted that the number average molecular weight of the flexible intrinsically thermally conductive polysiloxane composite material in the embodiment of the present invention is preferably 100,000.
[0056] It should be noted that in the above step S10, 4,4-dihydroxybiphenyl, 6-bromo-1-hexene and an alkaline catalyst are dissolved in a first organic solvent to carry out a dehydrobromination reaction, preferably the following steps: 4,4-dihydroxybiphenyl and the first organic solvent are mixed to obtain a 4,4-dihydroxybiphenyl solution; 6-bromo-1-hexene, potassium carbonate and potassium iodide are added to the 4,4-dihydroxybiphenyl solution in sequence.
[0057] It should be noted that, when 4,4-dihydroxybiphenyl and the first organic solvent are mixed, it is preferably carried out under magnetic stirring conditions; in the present invention, there is no particular limitation on the stirring rate and time, as long as the components can be mixed uniformly.
[0058] It should be noted that the preferred method of adding 6-bromo-1-hexene in the present invention is dropwise addition; and the present invention has no particular limitation on the dropwise addition rate and time, and the dropwise addition rate and time known to those skilled in the art can be used.
[0059] It should be noted that the above dehydrobromination reaction is carried out under water bath conditions; after the above dehydrobromination reaction is completed, the present invention preferably performs rotary evaporation, first drying, first washing, second washing and second drying on the reaction product in sequence to obtain the first compound.
[0060] It should be noted that in the present invention, the temperature of the first drying is preferably 65-85° C., and the drying time is preferably 12-24 hours. In the present invention, the first drying method is preferably vacuum drying; and the vacuum drying is preferably performed in a vacuum drying oven.
[0061] It should be noted that the washing liquid used in the first washing is preferably distilled water; the washing liquid used in the second washing is preferably anhydrous ethanol; the washing method is preferably to stir in the washing liquid for 24 hours and then filter, and the number of washing times for each washing liquid is preferably 2-4 times.
[0062] It should be noted that after washing, the present invention preferably dries the washed material.
[0063] It should be noted that the present invention does not impose any specific limitation on the parameters of the rotary evaporation, as long as the first organic solvent can be removed.
[0064] It should be noted that in the present invention, the temperature of the second drying is preferably 55-65° C., and the drying time is preferably 12-24 hours. In the present invention, the second drying method is preferably vacuum drying; and the vacuum drying is preferably performed in a vacuum drying oven.
[0065] In a specific embodiment, the hydrosilylation catalyst in the embodiment of the present invention is preferably one or more of chloroplatinic acid, Karstedt's catalyst and chloroplatinic acid complex.
[0066] It should be noted that the particle size of BNNs of different particle sizes is 1 μm to 15 μm, and preferably the two particle sizes are 1 μm and 10 μm, respectively, which are abbreviated as nBNNs and mBNNs.
[0067] It should be noted that the mixing of BNNs of different particle sizes, the first compound, vinyl-terminated polydimethylsiloxane, the hydrosilylation catalyst and dimethylmethyl hydrogen (siloxane and polysiloxane) in the above step S20 preferably includes the following steps: after the mBNNs and the vinyl-terminated polydimethylsiloxane are evenly mixed, the nBNNs and the first compound are added and stirred to obtain a mixture; the hydrosilylation catalyst is added to the above mixture, and after stirring, dimethylmethyl hydrogen (siloxane and polysiloxane) is added. The mixture is vacuumed to remove bubbles and poured into a mold. In the present invention, the mixing of BNNs of different particle sizes, the first compound, vinyl-terminated polydimethylsiloxane, Karstedt's catalyst and dimethylmethyl hydrogen (siloxane and polysiloxane) is preferably carried out under magnetic stirring.
[0068] In a specific embodiment, when the silicon-oxygen addition reaction is carried out in the embodiment of the present invention, the reaction temperature is preferably 110-120° C., and the reaction time is preferably 6-12 hours.
[0069] It should be noted that after the hydrosilylation reaction, the present invention preferably sequentially performs a first adsorption, a first filtration, a rotary evaporation, a first drying, a second extraction, a second rotary evaporation and a second drying on the obtained hydrosilylation reaction liquid to obtain the first compound.
[0070] The preparation method of the flexible intrinsic thermal conductive polysiloxane composite material provided by the present invention first uses 4,4-dihydroxybiphenyl, 6-bromo-1-hexene and an alkaline catalyst as main raw materials, and synthesizes a small molecule liquid crystal monomer through a dehydrobromination reaction; the dehydrobromination reaction product is subjected to a hydrosilylation reaction with a vinyl-terminated polydimethylsiloxane, a hydrosilylation catalyst and dimethylmethyl hydrogen (siloxane and polysiloxane) to prepare an intrinsic high thermal conductive polysiloxane, and is composited with BNNs of different particle sizes as fillers. On the one hand, the stacking of the rigid biphenyl group side chains and the π-π stacking structure between molecules inhibit the random orientation of the molecular chain, thereby promoting the formation of ordered domains of the layered structure. On the other hand, the compounding of BNNs of different particle sizes can construct a more efficient thermal conductive path, improve the thermal conductivity of the composite material, and give it low density and high volume resistivity.
[0071] In a specific embodiment, the molar ratio of 4,4-dihydroxybiphenyl and the 6-bromo-1-hexene in the embodiment of the present invention is 10:20-23; more preferably 10:21. Wherein, when the molar ratio of 4,4-dihydroxybiphenyl and 6-bromo-1-hexene is less than 10:23, due to the excess of 6-bromo-1-hexene, the dehydrobromination reaction is incomplete, so that a large amount of 6-bromo-1-hexene remains in the product; when the molar ratio of 4,4-dihydroxybiphenyl and 6-bromo-1-hexene is greater than 10:20, 4,4-dihydroxybiphenyl is excessive, and a large amount of 4,4-dihydroxybiphenyl remains in the product; when the molar ratio of 4,4-dihydroxybiphenyl and 6-bromo-1-hexene is preferably 10:21, the dehydrobromination reaction is completely carried out, and a small amount of 6-bromo-1-hexene remains, which can be completely removed by subsequent washing.
[0072] In a specific embodiment, the molar ratio of 4,4-dihydroxybiphenyl to the alkaline catalyst in the embodiment of the present invention is preferably 10:20-23. When the molar ratio of 4,4-dihydroxybiphenyl to the alkaline catalyst is less than 10:23, the alkaline catalyst is excessive and the alkaline catalyst remains in the product; when the molar ratio of 4,4-dihydroxybiphenyl to the alkaline catalyst is greater than 10:20, the 4,4-dihydroxybiphenyl is excessive, the alkaline catalyst cannot completely react with the hydroxyl group in the 4,4-dihydroxybiphenyl, the dehydrobromination reaction is incomplete, and the 4,4-dihydroxybiphenyl remains in the product.
[0073] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0074] In a specific embodiment, the alkaline catalyst in the embodiment of the present invention is preferably one or more of potassium carbonate, potassium iodide and potassium hydroxide; more preferably a mixture of potassium carbonate and potassium iodide.
[0075] The reaction mechanism of the alkaline catalyst is that the hydroxide ions in the alkaline catalyst act as nucleophiles to attack the halogen atoms in the organic halogen compound, causing it to release halogen atoms to generate a dehydrobromination reaction of an aromatic compound. The alkaline catalyst can promote the removal of halogen atoms from the halogen compound, causing p-hydroxybiphenyl to lose one molecule of alcohol to obtain one molecule of the first compound and hydrogen bromide.
[0076] It should be noted that, when the alkaline catalyst is a mixture of potassium carbonate and potassium iodide, the molar ratio of the first compound to potassium carbonate is preferably 10:21-23; more preferably 10:21.
[0077] In a specific embodiment, the temperature for the dehydrobromination reaction in the embodiment of the present invention is preferably 40-65° C., more preferably 60-65° C.; the reaction time is preferably 24-48 hours, more preferably 36-48 hours, and most preferably 40-48 hours.
[0078] In a specific embodiment, the first organic solvent in the embodiment of the present invention is preferably acetone, which has the advantage of having good solubility for reactants and can promote the forward progress of the reaction.
[0079] In a specific embodiment, the hydrosilylation catalyst in the embodiment of the present invention includes one or more of chloroplatinic acid, Karstedt's catalyst and chloroplatinic acid complex.
[0080] The hydrosilylation catalyst can promote the addition reaction between the carbon-carbon double bond on the first compound and the active hydrogen on dimethylmethyl hydrogen (siloxane and polysiloxane) to generate new silicon-carbon bonds.
[0081] In a specific embodiment, the particle sizes of BNNs in the embodiments of the present invention include 1 μm and 10 μm.
[0082] In a specific embodiment, the weight ratio of BNNs in the embodiment of the present invention to the total weight of vinyl-terminated polydimethylsiloxane, dimethylmethyl hydrogen (siloxane and polysiloxane) and the first compound is 10-30:90-70.
[0083] In a specific embodiment, the molar ratio of the sum of the first compound and the vinyl-terminated polydimethylsiloxane in the embodiment of the present invention to dimethylmethyl hydrogen (siloxane and polysiloxane) is preferably 1.4 to 1.6:1, wherein, when the molar ratio of the sum of the first compound and the vinyl-terminated polydimethylsiloxane to dimethylmethyl hydrogen (siloxane and polysiloxane) is less than 1.4:1, the reaction is incomplete, and a large amount of active hydrogen remains in the polysiloxane, which will undergo a cross-linking reaction with water and oxygen in the air, thereby reducing the flexibility of the polysiloxane; when the molar ratio of the sum of the first compound and the vinyl-terminated polydimethylsiloxane to dimethylmethyl hydrogen (siloxane and polysiloxane) is greater than 1.6:1, the first compound remains in the product, so that the liquid crystal small molecules do not have a good orientation effect, affecting the thermal conductivity.
[0084] It should be noted that, when the hydrosilylation catalyst is preferably Karstedt's catalyst, the molar ratio of the first compound to the Karstedt's catalyst is preferably 9.5-10.5:0.1, more preferably 10:0.1.
[0085] The technical method of the present invention will be further described below in conjunction with specific embodiments.
[0086] Example 1
[0087] This embodiment provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0088] (1) Dissolving 4,4-dihydroxybiphenyl, 6-bromo-1-hexene, potassium carbonate and potassium iodide in a first organic solvent and performing a dehydrobromination reaction to obtain a first compound:
[0089] The specific process is as follows: 3.724g (20mmol) 4,4-dihydroxybiphenyl, 5.796g (42mmol) potassium carbonate and 0.6g (7mmol) potassium iodide are dissolved in 70mL acetone, stirred until clear and transparent, and then 6.846g (42mmol) 6-bromo-1-hexene is slowly dripped thereinto, and the resulting mixture is condensed and refluxed at 60°C for 48 hours. Afterwards, the reaction mixture is cooled to room temperature, the excess solvent is removed by rotary evaporation, the product is washed with a large amount of deionized water, and then washed twice with ethanol. The filtrate is removed, the filter cake is collected, and the first compound is obtained after vacuum drying for 8 hours.
[0090] (2) The first compound, vinyl-terminated polydimethylsiloxane, a hydrosilylation catalyst and dimethylmethyl hydrogen (siloxane and polysiloxane) are subjected to a siloxane addition reaction to obtain an intrinsically highly thermally conductive polysiloxane:
[0091] The specific process is as follows: 0.35g (1mmol) of the first compound and 3.702g (0.5mmol) of vinyl-terminated polydimethylsiloxane are mixed and stirred evenly, 4μL of Karstedt's catalyst is added to the above mixture, and 8g (1mmol) of dimethyl methyl hydride (siloxane and polysiloxane) is added. The mixture is vacuumed to remove bubbles, poured into a mold, and reacted at 110°C for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material PDMS, whose intrinsic thermal conductivity is 0.34W / (m·K).
[0092] Example 2
[0093] This embodiment 2 provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0094] (1) Dissolving 4,4-dihydroxybiphenyl, 6-bromo-1-hexene, potassium carbonate and potassium iodide in a first organic solvent and performing a dehydrobromination reaction to obtain a first compound:
[0095] The specific process is as follows: 3.724g (20mmol) 4,4-dihydroxybiphenyl, 5.796g (42mmol) potassium carbonate and 0.6g (7mmol) potassium iodide are dissolved in 70mL acetone, stirred until clear and transparent, and then 6.846g (42mmol) 6-bromo-1-hexene is slowly dripped thereinto, and the resulting mixture is condensed and refluxed at 60°C for 48h. Afterwards, the reaction mixture is cooled to room temperature, the excess solvent is removed by rotary evaporation, the product is washed with a large amount of deionized water, and then washed twice with ethanol. The filtrate is removed, the filter cake is collected, and the first compound is obtained after vacuum drying for 8h.
[0096] (2) The BNNs of different particle sizes, the first compound, vinyl-terminated polydimethylsiloxane, a hydrosilylation catalyst and dimethylmethylhydrogen (siloxane and polysiloxane) are subjected to a siloxane addition reaction to obtain a flexible intrinsically thermally conductive polysiloxane composite material:
[0097] The specific process is as follows: (3.24g) mBNNs and 3.702g (0.5mmol) vinyl-terminated polydimethylsiloxane are mixed and stirred evenly, and (0.36g) nBNNs and 0.35g (1mmol) of the first compound are added to obtain a mixture 1; 4μL Karstedt's catalyst is added to the above mixture, and 8g (1mmol) dimethyl methyl hydrogen (siloxane and polysiloxane) is added. The mixture is vacuumed to remove bubbles, poured into a mold, and reacted at 110°C for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0098] It should be noted that the λ of the flexible intrinsically thermally conductive polysiloxane composite material is ∥ It is 12.5W / (m·K).
[0099] Example 3
[0100] This embodiment 3 provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0101] A flexible intrinsically thermally conductive polysiloxane composite material was prepared according to the method of Example 2, except that in step (2), (2.52 g) mBNNs and 3.702 g (0.5 mmol) vinyl-terminated polydimethylsiloxane were mixed and stirred evenly, (1.08 g) nBNNs and 0.35 g (1 mmol) of the first compound were added to obtain a mixture 1; 4 μL Karstedt's catalyst was added to the above mixture, and 8 g (1 mmol) dimethyl methyl hydrogen (siloxane and polysiloxane) was added. The mixture was evacuated to remove bubbles, poured into a mold, and reacted at 110° C. for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0102] It should be noted that the λ of the flexible intrinsically thermally conductive polysiloxane composite material is ∥ It is 10.6W / (m·K).
[0103] Example 4
[0104] This embodiment 4 provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0105] A flexible intrinsically thermally conductive polysiloxane composite material was prepared according to the method of Example 2, except that in step (2), (1.80 g) of mBNNs and 3.702 g (0.5 mmol) of vinyl-terminated polydimethylsiloxane were mixed and stirred evenly, and (1.80 g) of nBNNs and 0.35 g (1 mmol) of the first compound were added to obtain a mixture 1; 4 μL of Karstedt's catalyst was added to the above mixture, and 8 g (1 mmol) of dimethyl methyl hydrogen (siloxane and polysiloxane) was added. The mixture was evacuated to remove bubbles, poured into a mold, and reacted at 110° C. for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0106] It should be noted that the λ of the flexible intrinsically thermally conductive polysiloxane composite material is ∥ It is 9.7W / (m·K).
[0107] Example 5
[0108] This embodiment 5 provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0109] A flexible intrinsically thermally conductive polysiloxane composite material was prepared according to the method of Example 2, except that in step (2), (1.08 g) of mBNNs and 3.702 g (0.5 mmol) of vinyl-terminated polydimethylsiloxane were mixed and stirred evenly, and (2.52 g) of nBNNs and 0.35 g (1 mmol) of the first compound were added to obtain a mixture 1; 4 μL of Karstedt's catalyst was added to the above mixture, and 8 g (1 mmol) of dimethyl methyl hydrogen (siloxane and polysiloxane) was added. The mixture was evacuated to remove bubbles, poured into a mold, and reacted at 110° C. for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0110] It should be noted that the λ of the flexible intrinsically thermally conductive polysiloxane composite material is ∥ It is 8.6W / (m·K).
[0111] Example 6
[0112] This embodiment provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0113] (1) 20 mmol of 4,4-dihydroxybiphenyl was added to 70 mL of acetone, and the mixture was stirred magnetically to be uniform. Then, 44 mmol of potassium carbonate and 2 mmol of potassium iodide were added in sequence, and the mixture was stirred until clear and transparent. Subsequently, 46 mmol of 6-bromo-1-hexene was slowly added dropwise thereto, and the resulting mixture was condensed and refluxed at 50° C. for 40 hours. Thereafter, the reaction mixture was cooled to room temperature, the excess solvent was removed by rotary evaporation, and the mixture was dried. The mixture was stirred in a large amount of distilled water for 24 hours, and the product was washed four times. The product was stirred in anhydrous ethanol for 24 hours, and washed three times. The filtrate was removed, and the filter cake was collected. The first compound was obtained after vacuum drying at 60° C. for 8 hours.
[0114] A flexible intrinsically thermally conductive polysiloxane composite material was prepared according to the method of Example 2, except that in step (2), (0.36 g) mBNNs and 3.702 g (0.5 mmol) vinyl-terminated polydimethylsiloxane were mixed and stirred evenly, and (3.24 g) nBNNs and 0.35 g (1 mmol) of the first compound were added to obtain a mixture 1; 4 μL Karstedt's catalyst was added to the above mixture, and 8 g (1 mmol) dimethyl methyl hydrogen (siloxane and polysiloxane) was added. The mixture was evacuated to remove bubbles, poured into a mold, and reacted at 110° C. for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0115] It should be noted that the λ of the flexible intrinsically thermally conductive polysiloxane composite material is ∥ It is 8.0W / (m·K).
[0116] Example 7
[0117] This embodiment provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0118] (1) 20 mmol of 4,4-dihydroxybiphenyl was added to 70 mL of acetone, and the mixture was stirred magnetically to be uniform. Then, 44 mmol of potassium carbonate and 2 mmol of potassium iodide were added in sequence, and the mixture was stirred until clear and transparent. Subsequently, 46 mmol of 6-bromo-1-hexene was slowly added dropwise thereto, and the resulting mixture was condensed and refluxed at 50° C. for 40 hours. Thereafter, the reaction mixture was cooled to room temperature, the excess solvent was removed by rotary evaporation, and the mixture was dried. The mixture was stirred in a large amount of distilled water for 24 hours, and the product was washed four times. The product was stirred in anhydrous ethanol for 24 hours, and washed three times. The filtrate was removed, and the filter cake was collected. The first compound was obtained after vacuum drying at 60° C. for 8 hours.
[0119] (2) Mix mBNNs and 0.7 mmol vinyl-terminated polydimethylsiloxane, stir evenly, add nBNNs and 1.4 mmol first compound, and obtain mixture 1; add chloroplatinic acid catalyst to the above mixture and add dimethylmethylhydrogen (siloxane and polysiloxane), the molar ratio of the sum of the first compound and vinyl-terminated polydimethylsiloxane to dimethylmethylhydrogen (siloxane and polysiloxane) is preferably 1.5:1, the mass ratio of mBNNs to nBNNs is 1:1, and the ratio of the mass sum of mBNNs to nBNNs to the total mass of vinyl-terminated polydimethylsiloxane, dimethylmethylhydrogen (siloxane and polysiloxane) and the first compound is 20:80. The molar ratio of the first compound to chloroplatinic acid is 9.5:0.1, the mixture is vacuumed to remove bubbles, poured into a mold, and reacted at 110°C for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0120] Example 8
[0121] This embodiment provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0122] (1) 20 mmol of 4,4-dihydroxybiphenyl was added to 70 mL of acetone, and the mixture was stirred magnetically to be uniform. Then, 44 mmol of potassium carbonate and 2 mmol of potassium iodide were added in sequence, and the mixture was stirred until clear and transparent. Subsequently, 46 mmol of 6-bromo-1-hexene was slowly added dropwise thereto, and the resulting mixture was condensed and refluxed at 50° C. for 40 hours. Thereafter, the reaction mixture was cooled to room temperature, the excess solvent was removed by rotary evaporation, and the mixture was dried. The mixture was stirred in a large amount of distilled water for 24 hours, and the product was washed four times. The product was stirred in anhydrous ethanol for 24 hours, and washed three times. The filtrate was removed, and the filter cake was collected. The first compound was obtained after vacuum drying at 60° C. for 8 hours.
[0123] (2) Mix mBNNs and 0.7 mmol vinyl-terminated polydimethylsiloxane, stir evenly, add nBNNs and 1.4 mmol first compound, and obtain mixture 1; add chloroplatinic acid catalyst to the above mixture and add dimethylmethylhydrogen (siloxane and polysiloxane), the molar ratio of the sum of the first compound and vinyl-terminated polydimethylsiloxane to dimethylmethylhydrogen (siloxane and polysiloxane) is preferably 1.6:1, the mass ratio of mBNNs to nBNNs is 1:1, and the ratio of the mass sum of mBNNs to nBNNs to the total mass of vinyl-terminated polydimethylsiloxane, dimethylmethylhydrogen (siloxane and polysiloxane) and the first compound is 10:90. The molar ratio of the first compound to the total molar ratio of chloroplatinic acid and chloroplatinic acid is 10.5:0.1, the mixture is vacuumed to remove bubbles, poured into a mold, and reacted at 110°C for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0124] Example 9
[0125] This embodiment provides a method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, and the specific steps are as follows:
[0126] (1) 20 mmol of 4,4-dihydroxybiphenyl was added to 70 mL of acetone, and the mixture was stirred magnetically to be uniform. Then, 44 mmol of potassium carbonate and 2 mmol of potassium iodide were added in sequence, and the mixture was stirred until clear and transparent. Subsequently, 46 mmol of 6-bromo-1-hexene was slowly added dropwise thereto, and the resulting mixture was condensed and refluxed at 50° C. for 40 hours. Thereafter, the reaction mixture was cooled to room temperature, the excess solvent was removed by rotary evaporation, and the mixture was dried. The mixture was stirred in a large amount of distilled water for 24 hours, and the product was washed four times. The product was stirred in anhydrous ethanol for 24 hours, and washed three times. The filtrate was removed, and the filter cake was collected. The first compound was obtained after vacuum drying at 60° C. for 8 hours.
[0127] (2) Mix mBNNs and 0.8 mmol vinyl-terminated polydimethylsiloxane, stir evenly, add nBNNs and 1.6 mmol first compound, and obtain mixture 1; add chloroplatinic acid catalyst to the above mixture and add dimethylmethylhydrogen (siloxane and polysiloxane), the molar ratio of the sum of the first compound and vinyl-terminated polydimethylsiloxane to dimethylmethylhydrogen (siloxane and polysiloxane) is preferably 1.4:1, the mass ratio of mBNNs to nBNNs is 1:1, and the ratio of the mass sum of mBNNs to nBNNs to the total mass of vinyl-terminated polydimethylsiloxane, dimethylmethylhydrogen (siloxane and polysiloxane) and the first compound is 30:70. The molar ratio of the first compound to chloroplatinic acid is 9.5:0.1, the mixture is vacuumed to remove bubbles, poured into a mold, and reacted at 110°C for 8 hours to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
[0128] Example 10
[0129] A polymer composite material comprises a flexible intrinsically thermally conductive polysiloxane composite material.
[0130] In order to analyze the structure of the flexible intrinsically thermally conductive polysiloxane composite material prepared in Example 1 of the present invention, a nuclear magnetic resonance hydrogen spectrum analysis was performed on the first compound provided in Example 1 of the present invention. The results are as follows: Figure 1 shown.
[0131] from Figure 1It can be seen that 6.8ppm and 7.4ppm are characteristic peaks of protons on the biphenyl structure, the multiple peaks at 4.9ppm and 5.7ppm are characteristic peaks of protons on unsaturated carbon-carbon double bonds, and 1.4ppm, 1.7ppm, 2.1ppm and 4.0ppm are characteristic peaks of protons on carbon-carbon chains. This proves that there are biphenyl elements connected by flexible carbon-carbon chains in the molecular structure. It is thus judged that the results of the flexible intrinsic thermal conductive polysiloxane composite material in Example 1 are the results shown in the present invention.
[0132] In order to verify the liquid crystal properties of the first compound prepared in Example 1 of the present invention, i.e., the small molecule liquid crystal monomer, the first compound prepared in Example 1 was characterized by polarizing microscopy. The results are as follows: Figure 2 shown.
[0133] from Figure 2 It can be seen that the observation area appears bright yellow at room temperature ( Figure 2 In (a), the boundaries between the small molecule liquid crystal monomer particles are clear, indicating that there is microscopic anisotropy in its structure, indicating that the small molecule liquid crystal monomer is a semi-crystalline compound. When the temperature rises to the crystal melting temperature (T lc , the temperature at which the crystal phase transforms into the liquid crystal phase), the small molecule liquid crystal monomer exhibits fluidity, and the field of view of the observation area gradually becomes brighter and more uniform ( Figure 2 (b) indicates that the small molecule liquid crystal monomer has changed from the crystalline state to the liquid crystal state. As the temperature rises further, the bright yellow and green spots (typical nematic phase morphology) disappear, and the field of view is completely transparent ( Figure 2 (c)), indicating that the temperature reaches the clearing point (T i , the temperature at which the liquid crystal phase changes to the isotropic phase), the small molecule liquid crystal monomer presents an isotropic liquid state. Therefore, the cross-linking temperature of the flexible intrinsic thermal conductive polysiloxane composite material is determined to be 120°C.
[0134] In order to verify the influence of different particle sizes of BNNs on the filler orientation order in the flexible intrinsic thermal conductive polysiloxane composite materials prepared in Examples 2-6 of the present invention, the flexible intrinsic thermal conductive polysiloxane composite materials prepared in Examples 2-6 were characterized by scanning electron microscopy. The results are as follows: Figure 3 shown.
[0135] from Figure 3 It can be seen from (a)-(e) that as the ratio of nBNNs:mBNNs increases, the distribution of fillers in the matrix gradually changes from ordered to disordered. This is because when the filler dosage reaches 30wt%, the ordered lamellar structure boron nitride forms a layered heat conduction path, which can effectively improve the heat transfer efficiency of the heat flow inside the composite material. This explains why the thermal conductivity decreases with the increase of the ratio of nBNNs:mBNNs when the mass fraction is 30wt.
[0136] The thermal conductivity of the flexible intrinsically thermally conductive polysiloxane composite material of the present invention was tested using a Hot Disk TPS2200 thermal conductivity tester. When the amount of BNNs was 30wt%, and the ratio of nBNNs:mBNNs was 1:9, 3:7, 5:5, 7:3 and 9:1, respectively, the λ ∥ They are 12.5W / (m·K), 10.6W / (m·K), 9.7W / (m·K), 8.6W / (m·K) and 8.0W / (m·K) respectively.
[0137] In order to verify the influence of volume resistivity in the flexible intrinsically thermally conductive polysiloxane composite materials prepared in Examples 2-6 of the present invention, the volume resistivity of the flexible intrinsically thermally conductive polysiloxane composite materials prepared in Examples 2-6 was tested. The results are as follows: Figure 4 shown.
[0138] from Figure 4 It can be seen that with the increase of nBNNs:mBNNs, the volume resistivity of the flexible intrinsic thermal conductive polysiloxane composite material gradually increases. This is because with the increase of nBNNs:mBNNs, the number of interfaces in the composite material increases significantly, and the increase in interfaces is the main reason for the increase in its volume resistivity. When the amount of BNNs is 30wt% and the ratio of nBNNs:mBNNs is 9:1, the volume resistivity of the flexible intrinsic thermal conductive polysiloxane composite material is as high as 1.85×10 14 Ω·cm.
[0139] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A flexible intrinsically thermally conductive polysiloxane composite material, characterized in that: The structural formula is as follows: Among them, the value range of n is 0 to 182, the value range of m is 0 to 182, and the value range of p is 23 to 45.
2. The flexible intrinsically thermally conductive polysiloxane composite material according to claim 1, characterized in that: The number average molecular weight of the flexible intrinsically thermally conductive polysiloxane composite material is 50,000-100,000.
3. The flexible intrinsically thermally conductive polysiloxane composite material according to claim 1, characterized in that: The relationship between n and m is n+m=182.
4. A method for preparing a flexible intrinsically thermally conductive polysiloxane composite material, characterized in that: The following steps are involved: Dissolving 4,4-dihydroxybiphenyl, 6-bromo-1-hexene and a basic catalyst in a first organic solvent, and performing a dehydrobromination reaction to obtain a first compound; Boron nitride nanosheets of different particle sizes, the first compound and vinyl-terminated polydimethylsiloxane are uniformly mixed, dimethyl methyl hydrogen (siloxane and polysiloxane) and a hydrosilylation catalyst are added to obtain a flexible intrinsically thermally conductive polysiloxane composite material.
5. The method for preparing the flexible intrinsically thermally conductive polysiloxane composite material according to claim 4, characterized in that: The molar ratio of the 4,4-dihydroxybiphenyl to the 6-bromo-1-hexene is 10:20-23; The molar ratio of the 4,4-dihydroxybiphenyl to the alkaline catalyst is 10:20-23.
6. The method for preparing the flexible intrinsically thermally conductive polysiloxane composite material according to claim 4, characterized in that: The alkaline catalyst is one or more of potassium carbonate and potassium iodide; The first organic solvent is acetone; The hydrosilylation catalyst is one or more of chloroplatinic acid, Karstedt's catalyst and chloroplatinic acid complex.
7. The method for preparing the flexible intrinsically thermally conductive polysiloxane composite material according to claim 4, characterized in that: The molar ratio of the first compound to the vinyl-terminated polydimethylsiloxane is 1:0.5; The molar ratio of the sum of the molar amounts of the first compound and the vinyl-terminated polydimethylsiloxane to the dimethyl methyl hydrogen (siloxane to polysiloxane) is 1.4 to 1.6:1; The molar ratio of the first compound to the hydrosilylation catalyst is 9.5-10.5:0.1; The ratio of the weight of the boron nitride nanosheets to the total weight of the vinyl-terminated polydimethylsiloxane, dimethylmethyl hydrogen (siloxane and polysiloxane) and the first compound is 10-30:90-70.
8. The method for preparing the flexible intrinsically thermally conductive polysiloxane composite material according to claim 4, characterized in that: The temperature for the dehydrobromination reaction is 60° C. and the reaction time is 12-24 hours; The temperature for the silicon-oxygen addition reaction is 110-120° C., and the reaction time is 6-12 hours.
9. The method for preparing a flexible intrinsically thermally conductive polysiloxane composite material according to claim 4, characterized in that: The particle size of the boron nitride nanosheets with different particle sizes ranges from 1 μm to 15 μm.
10. A polymer composite material, characterized in that: The invention comprises the flexible intrinsically thermally conductive polysiloxane composite material according to any one of claims 1 to 3 or the flexible intrinsically thermally conductive polysiloxane composite material prepared by the method according to any one of claims 4 to 9.
Citation Information
Patent Citations
Preparation method of mixed double-coated boron nitride / graphene insulating heat-conducting silicone grease
CN112280307A
Heat-conducting insulating high polymer material composite film based on boron nitride filler and preparation method of heat-conducting insulating high polymer material composite film
CN115572486A
Intrinsic high-thermal-conductivity polysiloxane, preparation method thereof and high polymer material
CN118772416A